2019
DOI: 10.1002/ar.24065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Marrow‐Derived Mesenchymal Stem Cells on Cochlear Function in an Experimental Rat Model

Abstract: Mesenchymal stem cell (MSC) therapy is an emerging treatment modality for various human diseases. Although induced pluripotent stem cells have been explored for the restoration of hearing, the potential of MSCs as a therapeutic strategy for various cochlear insults is not precisely known. MSCs possess anti‐inflammatory, anti‐apoptotic and neuroprotective properties, making them an attractive target for the treatment of inner ear disorders such as hair cell damage in response to inflammation. Most of the previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The transtympanic administration of BM-MSCs has no significant effect on the hearing thresholds, as determined based on ABR and distortion product otoacoustic emissions (DPOAE), which can be used to measure outer hair cell function. Histopathological examination did not reveal recruitment of inflammatory leukocytes and edema in the cochlea of MSCs administered in rats [67].…”
Section: Administration Of Stem Cells Into the Inner Earmentioning
confidence: 79%
“…The transtympanic administration of BM-MSCs has no significant effect on the hearing thresholds, as determined based on ABR and distortion product otoacoustic emissions (DPOAE), which can be used to measure outer hair cell function. Histopathological examination did not reveal recruitment of inflammatory leukocytes and edema in the cochlea of MSCs administered in rats [67].…”
Section: Administration Of Stem Cells Into the Inner Earmentioning
confidence: 79%
“…In mice, BMSCs were shown to enhance the regeneration and maintenance of fibrocytes in damaged SLs, leading to partial restoration of cochlear function [81]. Transtym-panic transplantation of rodent BMSCs in a non-immunocompromised rat model to assess cochlear function by ABR, distortion product otoacoustic emissions (DPOAE), and histopathology did not reveal the recruitment of inflammatory leukocytes and edema in the cochlea of MSCs administered rats [82]. Fetoni et al, in a noise deafened adult Guinea pig, found that transplanted AdSCs into scala tympani, via round window, were able to survive and migrate, at the site of tissue damage, and express trophic factors to pave the way for further treatment of deafness [83].…”
Section: In Vivo Studies Of Inner Ear Hearing Lossmentioning
confidence: 99%
“…In contrast, PSCs (embryonic stem cells [ESCs] and induced pluripotent stem cells [iPSCs]) have infinite self-renewal capacity and the ability to differentiate into any cell type of the three major germ layers. Somatic stem cells, such as mesenchymal stem cells and neural stem cells, have been used to generate inner ear progenitors and restore damaged spiral ganglia ( Boddy et al., 2012 , Mittal et al., 2020 , Xu et al., 2016 ). However, there are a limited number of sources for these somatic stem cells and they exhibit a restricted capacity for differentiation ( Clevers, 2015 ).…”
Section: Main Textmentioning
confidence: 99%